H∞ optimization‐based fractional‐order PID controllers design1. (10th July 2013) - Padula, F.; Vilanova, R.; Visioli, A.
SUMMARY In this paper we propose a fractional‐order proportional‐integral‐derivative controller design based on the solution of an <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh21k9hnhs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H∞</alternatives> model matching problem for fractional first‐order‐plus‐dead‐time processes. Starting from the analytical solution of the problem, we show that a fractional proportional‐integral‐derivative suboptimal controller can be obtained. Guidelines for the tuning of the controller parameters are given in order to address the robust stability issue and to obtain the required performance. The main differences with respect to the integer‐order case are highlighted. Simulation results show that the design methodology is effective and allows the user to consider process with different dynamics in a unified framework. Copyright © 2013 John Wiley & Sons, Ltd.